'Driven by Tens’: Obsession and cognitive difference in Toni Jordan’s romantic comedy Addition - Robertson, Rachel (Intellect Ltd, 2014)
This article explores how contemporary romance can represent cognitive disability through a critical analysis of the representation of cognitive difference in the romantic comedy Addition by Australian author Toni Jordan. I argue that the novel presents a non-stereotypical representation of a protagonist with a cognitive disability who is still able to participate in a love relationship while experiencing significant impairment. I argue that such works of popular romantic fiction can act to challenge negative stereotypes around mental illness and encourage readers to reflect on their own beliefs and attitudes.